Unexpected Coexisting Myocardial Infarction Detected by Delayed Enhancement MRI - Edouard Gerbaud; Henri De Clermont-Galleran; Matthew Erickson; Pierre Coste; Michel Montaudon (Case Reports in Medicine)
We report a case of an unexpected coexisting anterior myocardial infarction detected by delayed enhancement MRI in a 41-year-old man following a presentation with a first episode of chest pain during inferior acute myocardial infarction. This second necrotic area was not initially suspected because there were no ECG changes in the anterior leads and the left descending coronary artery did not present any significant stenoses on emergency coronary angiography. Unrecognised myocardial infarction may carry important prognostic implications. CMR is currently the best imaging technique to detect unexpected infarcts.